lncRNA DLX6-AS1 Promotes Myocardial Ischemia-Reperfusion Injury through Mediating the miR-204-5p/FBXW7 Axis - Fanshun Wang; Yuan Wu (Hindawi Limited, 2023)
Myocardial ischemia-reperfusion (IR) injury is the restoration of blood flow post ischemia, which threatens the human life. Long noncoding RNA distal-less homeobox 6 antisense 1 (DLX6-AS1) has been found to take part in the IR-induced cerebral injury. Here, we determined the functional role of DLX6-AS1 in IR-induced myocardial injury. We ligated the left anterior descending coronary artery of rats to induce IR injury. IR injury rats exhibited severe tissue damage and increase of infraction size. The levels of lactate dehydrogenase (LDH), creatine kinase (CK), proinflammatory factors including MCP-1, IL-6, and IL-1β, and cell apoptosis were also enhanced in IR rats, indicating that IR induced significant myocardial injury in rats. DLX6-AS1 expression was elevated in the myocardial tissues of IR injury rats, while DLX6-AS1 deficiency alleviated IR-induced myocardial injury in rats by reducing inflammatory response and cell apoptosis. Moreover, rat embryonic cardiomyocyte cell line H9c2 was subjected to hypoxia reoxygenation (HR). DLX6-AS1 was upregulated in the HR-treated H9c2 cells, and DLX6-AS1 enhanced the expression of F-box and WD40 repeat domain-containing 7 (FBXW7) by sponging miR-204-5p. Inhibition of DLX6-AS1 inhibited inflammatory response and cell apoptosis in H9c2 cells via miR-204-5p/FBXW7 axis. In conclusion, this work demonstrates that DLX6-AS1 accelerates myocardial IR injury through regulating miR-204-5p/FBXW7 axis. Thus, this work provides a novel ceRNA DLX6-AS1/miR-204-5p/FBXW7 axis in myocardial IR injury, and DLX6-AS1 may be a potential target for the treatment of myocardial IR injury.